Assessing Young Students' Design Thinking Disposition and Its Relationship With Computer Programming Self-Efficacy. (June 2021) - Tsai, Meng-Jung; Wang, Ching-Yeh
To explore the role of design thinking in contemporary computer literacy education, this study aimed to examine the relationship between young students' design thinking disposition and their computer programming self-efficacy. To assess students' design thinking disposition, this study developed the Design Thinking Disposition Scale (DTDS) with a sample of 350 junior high school students who had computer programming experience in a STEAM course. A principle axis factor analysis with the promax rotation method was used to verify the DTDS's construct under the four dimensions: empathize, define, ideate and prototype . The Cronbach's alpha reliability was .90 for the overall scale. Correlation analyses results showed that all the four dimensions were significantly correlated with computer programming self-efficacy assessed by CPSES. A significant regression model was found in which the three factors, ideate, prototype and define, significantly predicted the overall computer programming self-efficacy. Meanwhile, except for the ideate subscale, no gender difference was found in the young students' design thinking dispositions. The students' self-directed programming learning experience was shown to benefit their design thinking disposition. The DTDS can be applied to design-thinking-embedded computer literacy curricula such as makers, STEAM, or robotics education. Several further studies are also suggested.